PENGARUH CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE OPPO - Winda Larika; Sri Ekowati (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This study aimed at finding out the effect of brand image, price, and promotion of the Oppo Mobile Purchasing Decision (Case Study of Management Students in the Private Universities of Bengkulu City). This type of study employed a sample of 266 people taken using the cluster sampling method. Data were collected using a questionnaire. The data analysis techniquewasusing multiple linear regression, coefficient of determination (R2), hypothesis testing. Based on the results of this study, it can be seen that Brand Image has a significant effect on the Oppo Mobile Purchasing Decision on the Management students Department of Private Universities, Bengkulu City. The price affected significantly on the Oppo Mobile Purchasing Decision in the Management Department students of Bengkulu City privateuniversities. Promotion predisposed on the Oppo Mobile Purchasing Decision in the Management Department student of Bengkulu City privateuniversities as well. Based on the coefficient of determination test, it has the meaning thatBrand Image (X1), Price (X2) and Promotion (X3) contributed significantly contribution of 64.6% of the Oppo Mobile Purchase Decision (Y) on the Management Department students of Bengkulu Private University, while 25.4% was swayed by other variables not included in this study.